A CFD study on the effect of compression ratio on combustion characteristics and emissions in a spark-ignition engine. (2nd September 2020) - Gupta, Sachin Kumar; Mittal, Mayank
The variable compression ratio is a viable technology to improve engine performance and to reduce greenhouse gas emissions. In the present study, numerical simulations were performed to quantify the effect of compression ratio (CR) on the characteristics of a spark-ignition (SI) engine. The simulations were carried out using Converge CFD with detailed chemical kinetics. The validation study for gasoline-driven SI engine, having bowl-in-piston and flat head type configuration, with CR of 8.5:1 showed that the numerical framework was accurate enough to predict the combustion characteristics of the engine. After verifying the model, a parametric study was conducted at different spark timings and CRs. Results showed that the indicated thermal efficiency increased by 3.4% and emission levels of carbon dioxide and carbon monoxide decreased by 11.8% and 8.1% when CR was increased from 8.5:1 to 12:1, respectively. Also, the flame velocity was found to be increased with the increase in CR.